Lowering iron losses during slag removal in hot metal desulphurisation without using fluoride. (27th May 2020) - Schrama, Frank N. H.; Ji, Fuzhong; Hunt, Adam; Beunder, Elisabeth M.; Woolf, Rhian; Tuling, Alison; Warren, Peter; Sietsma, Jilt; Boom, Rob; Yang, Yongxiang
ABSTRACT: To lower the iron losses of the hot metal desulphurisation (HMD) process, slag modifiers can be added to the slag. Slag modifiers decrease the apparent viscosity of the HMD slag. Most common slag modifiers in industry contain fluoride as a fluidiser. However, fluoride leads to a higher magnesium consumption and has health, safety and environment issues. Fluoride-free alternatives like nepheline syenite (NS) and fly ash (or pulverised fuel ash, PFA) can decrease the slag's apparent viscosity. Experiments with HMD slags containing CaF2, NS and PFA and without slag modifier were performed for slags with a high and an average basicity. The melting points of the slags and their viscosities 1250–1600°C were measured. The experimental results are compared with FactSage calculations. PFA and NS are viable alternatives in the industrial HMD process, as reasonable amounts are sufficient to reach the same lower apparent viscosities and melting points as with CaF2 .